Drowning Death: A Literature Review - Khaerunnisah; Aji, Ario Seno; Ramadhani, Nadia; Salsabila, Naura Hasna; Pitaloka, Azizah Shiena (Jurnal Medis Islam Internasional, 2022)
Background: The process of drowning begins with respiratory distress either because a person's airway is below the surface of the liquid (submersion) or the water only covers the face (immersion) (Putra, 2020). In a body submerged in water and suspected of having died from drowning, it is necessary to determine whether the victim was still alive at the time of the drowning. The probability was marked by intravital signs, whether there were other signs of violence or the cause of death. All these things can be determined through an external and internal body examination of the corpse and are supported by supporting examinations. With this series of examinations, the diagnosis of drowning can be established, and the cause and mechanism of death of the bodies found can be estimated. Doctors in forensic medicine have an important role in cases of drowning deaths, such as in helping to identify victims and determine the cause of death. (Armstrong & Erskine, 2018). Objective: This report aims to learn more about drowning deaths, the classification, the pathophysiology of drowning deaths, and the process of investigating drowning deaths. Conclusion: Drowning is asphyxia that prevents air entry into the lungs by inhaling fluid into the airways, i.e., nose and mouth. Cases of drowning death are caused by irreversible brain damage in the development of irreversible cerebral anoxia and hypoxia. There are two classifications of drowning, namely Dry Drowning and Wet Drowning. Doctors in the field of forensic medicine have an important role in cases of drowning deaths, such as in helping efforts to identify victims and determine the cause of death. The investigation process includes Pre-Autopsy Preparation and Interest in Victim History, External Findings, Internal Meetings, and Special Tests.